PENGARUH PENDEKATAN REALISTIC MATEMATIC EDUCATION TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR SISWA - Maya Syntya (Pendidikan Matematika | STKIP YM Bangko, 2020)
The purpose of this study is to describe the ability of mathematical representation taught with realistic matematic education approaches better than conventional learning of students of class VIII of SMP Negeri 2 Merangin in the academic year 2019/2020. This research uses a quantitative approach with an experimental method. The sampling technique uses simple random sampling. The samples are grouped based on high, medium and low learning independence. Data collection techniques using test and non-test. The analysis technique uses u-test, t-test and two-way ANOVA. The test results state that: the ability of mathematical representation with medium and low learning independence with realistic mathematical education approaches is better than conventional approaches, whereas with high learning independence conventional approaches are better than realistic mathematical education approaches, and there is an interaction between realistic matematic education and conventional approaches in terms of the independence of student learning.